2016
DOI: 10.1002/adma.201604003
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastrong Boron Frameworks in ZrB12: A Highway for Electron Conducting

Abstract: ZrB , with a high symmetrical cubic structure, possesses both high hardness ≈27.0 GPa and ultralow electrical resistivity ≈18 µΩ cm at room temperature. Both the superior conductivity and hardness of ZrB are associated with the extended BB 3D covalent bonding network as it is not only favorable for achieving high hardness, but also provides conducting channels for transporting electrons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
79
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 81 publications
(90 citation statements)
references
References 47 publications
9
79
0
Order By: Relevance
“…Metal borides constitute a class of materials that are still exotic to most chemists and material scientists, despite some excellent properties that have led to some key industrial applications such as hard magnets (Nd 2 Fe 14 B), superconductors (MgB 2 ), bulk refractory and conductive ceramics (ZrB 2 , HfB 2 ), and hard materials (TiB 2 ) . Also, several other properties of bulk metal borides have been the focus of many recent investigations, these include super hardness, thermoelectric and magnetic properties, materials for batteries, and catalysts . Transition metal boride materials have attracted considerable attention in recent years.…”
mentioning
confidence: 99%
“…Metal borides constitute a class of materials that are still exotic to most chemists and material scientists, despite some excellent properties that have led to some key industrial applications such as hard magnets (Nd 2 Fe 14 B), superconductors (MgB 2 ), bulk refractory and conductive ceramics (ZrB 2 , HfB 2 ), and hard materials (TiB 2 ) . Also, several other properties of bulk metal borides have been the focus of many recent investigations, these include super hardness, thermoelectric and magnetic properties, materials for batteries, and catalysts . Transition metal boride materials have attracted considerable attention in recent years.…”
mentioning
confidence: 99%
“…The observed data can be well described by 1 0 = 6.4 mW cm À1 and A = 5.7 10 À4 mW cm À K À2 .T he residual resistivity ratio was defined as 1 (300 K) /1 0 = 7.0, which is very small for the contribution of impurity or grain boundary to the resistivity.T he resistivity at room temperature is about 45 mW cm À1 ,c omparable to some metals and metal alloys, such as CrB, VB 2 andZ rB 12 . [17,28,47] Indeed,t antalumm onoboride has ag ood balance between hardnessa nd electrical conductivity. This feature demonstrates that Ta Bi sa"covalent metal" compound.…”
Section: Resultsmentioning
confidence: 99%
“…Many boridesw ith extremely high boron content, such as tetraborides (WB 4 ,C rB 4 ,F eB 4 ,M nB 4 )a nd even dodecaborides (ZrB 12 ,S cB 12 ,Y B 12 ), have been synthesized. [23][24][25][26][27][28] However,i ti s still challenging to incorporate more boron atoms into most transition metal latticesw ith aB:TM molar ratio exceeding 4:1, due to their harsh synthesis conditions. Additionally,h igher boron content, especiallyt hat is highert han 4:1, will suppress the mobility of d-electrons in transition metal atoms owing to the strong hybridization between TMs d-orbital and LEs 2p-orbital.…”
Section: Introductionmentioning
confidence: 99%
“…[22][23][24][25][26][27] Namely, the boron concentration plays an important role in mechanical properties of the TMBs. [28,29] In particular, the TMB 12 has a boron cuboctahedron cage, which is composed of 24 B atoms. The recent work has been shown that the TMB 12 is a potential superhard material because of the network B-B covalent bonds.…”
Section: Introductionmentioning
confidence: 99%